The relevance of implementing comprehensive security concept (COMSEC) towards the endemic era of covid-19 - Irma Wani Othman; Saifulazry Mokhtar; Azmin Pullong (Global Academic Excellence, 2022)
The discussion in this paper refers to Comprehensive Security (COMSEC) as a continuous effort that is balanced, integrated at every level of government administration and societal structure and across all fields. In order to maintain the Federation of Malaysia’s sovereignty, peace and prosperity, it is necessary to protect the country from all internal and external dangers. This paper discusses COMSEC and its relationship to the sovereignty and security of our nation, Malaysia. The discussion’s focus has shifted when a number of issues were brought up, including the problem of cross-border crime and the current digital threat, where it is important to comprehend COMSEC in order to deal with the Covid-19 outbreak and build public awareness and resilience in order to ensure national security and sustainable development, which is the key to sustainable development. The primary objective of this discussion is to identify the issues that play a significant role in the government’s attempts to implement COMSEC, as well as the challenges faced by the government in addressing the contested issues. The qualitative approach used in this writing uses secondary sources such published study findings, academic writing, online news sources, and public forums. The issue of cross-border crime, such as smuggling, human trafficking, and the invasion of illegal Immigrants (PATI) continues to plague the majority of developing nations, including Malaysia. The problem of digital threats also sparked alarm among the public and the government, since it is one of the issues the government faces in ensuring the security and sovereignty of the nation. In the meantime, there are doctrines regarding the implementation of COMSEC that are still applicable in the current day, but they should be modified to reflect the changing patterns of the times. According to the findings of the study, the government also had a crucial role in preventing the growth of the Covid-19 outbreak in Malaysia. However, other parties also play a crucial role in breaking the chain of the Covid-19 epidemic. Especially in this epidemic period, all parties must work together to realise the government’s goals so that the safety of the people and the nation can be ensured through the application of the COMSEC concept.